Thermodynamics-antioxidant activity relationships of some 4-benzylidenamino-4, 5-dihydro-1h-1, 2, 4-triazol-5-one derivatives: Theoretical evaluation. Issue 9 (2nd September 2017) - Zobo Mfomo, Joseph; Bikele Mama, Désiré; Lissouck, Daniel; Younang, Elie; N'sikabaka, Samuel; Mbouombouo Ndassa, Ibrahim; Mbaze Meva'à, Luc
ABSTRACT: Density functional methods were used to predict the antioxidative efficiency of thirteen 4-benzylidenamino-4, 5-dihydro-1H-1, 2, 4-triazol-5-one derivatives in the gas phase and in the solution phase (water and benzene). Optimized geometries of molecules and reaction thermodynamic energies (enthalpies and reaction-free energies) of three main antioxidant mechanisms (hydrogen atom transfer, single electron transfer-proton transfer, and sequential proton loss electron transfer) were studied at B3LYP/6-31G (d, p) level. Solvent contributions to thermodynamic energies were computed employing integral equation formalism integral equation formalism polarized continuum model method. Obtained results revealed that the three main working mechanisms were endothermic, but not spontaneous especially in the gas phase. We found that the single electron transfer process from the anionic form was more preferable than that from the neutral form in the gas phase. The comparison of the ionization potentials of 4-benzylidenamino-4, 5-dihydro-1H-1, 2, 4-triazol-5-one derivatives to those of classical antioxidants (gallic acid, caffeic acid, ferulic acid, and ascorbic acid) indicated that the electron transfer mechanism was more predominant in the thirteen 4-benzylidenamino-4, 5-dihydro-1H-1, 2, 4-triazol-5-one derivative compounds. Thermodynamically, single electron transfer process from the anionic form was the most preferable mechanism in the gas phase. Solvent effect drastically modified thermodynamic energies of mechanisms. The proton transfer process was the thermodynamically favored mechanism as compared to other mechanisms in both solvents. It is worth mentioning that all the mechanisms were found not to be spontaneous in the solution phase except the proton transfer process.